Inside Back Cover: Nano‐therapeutic strategies to target coronavirus (View 3/2021). Issue 3 (17th June 2021) - Rauf, Mohd Ahmar; Tasleem, Munazzah; Bhise, Ketki; Tatiparti, Katyayani; Sau, Samaresh; Iyer, Arun K.
Abstract : The use of nanoparticles as vectors for therapeutic agent delivery against COVID‐19. In the image of article number 20200155, Arun K. Iyer and co‐workers have proposed the utility of different nanoparticle systems including polymeric nanoparticles, antibody‐drug conjugates, solid‐lipid nanoparticles, and siRNA‐based technologies for treating COVID‐19. The nanoparticles can be conjugated or encapsulated with potent anti‐viral agents such as remdesivir and favipiravir, for infection selective delivery. The nanoparticles can protect the drug from degradation in transit, enable controlled release of drug at sites of infection and limit their off‐target effects in non‐target organs and tissues, thereby improving patient compliance and safety.